ANALISIS KUALITAS PEMBIAYAAN PERBANKAN SYARIAH TAHUN 2006-2010 - Indriana, Dewi; Zuhroh, Idah (Jurnal Ekonomi Pembangunan, 2012)
The research is quantitative descriptive research done in three banks titled: â€œAnalysis of Financing Quality in Syariah Banks Period 2006-2010â€. The research purpose is to find out how much given debt influenceÂ  and Loan to Assets Ratio (LAR) to Non Performing Loan. In this research, researcher took hypothesis that thereâ€™s a significant influence between given debt, Loan to Assets Ratio (LAR) to Non Performing Loan in Syariah Banks period 2006-2010. From the result, it is found determination coefficient (R2) for data regression 0,467. It means that independence variable altogether are able to explain 47% variance of dependent variables, which is Non Performing Loan. Then from t test, it is found that given-debt variable has significant influence to NPL, it is proven that Tcount > Ttable, while LAR has unsignificant influence, itâ€™s proven that Tcount < Ttable and after f test, it is found that given-debt variable and LAR overall has significant influence to NPL. Â From data analysis done at once, itâ€™s shown that debt variable given has more significant result to NPL than LAR, which is 0,677%.Â